Evaluation of factors influencing adherence to treatment with sodium-glucose cotransporter type 2 inhibitor - D. A. Lebedev; A. A. Mosikian; A. Yu. Babenko (Бюллетень сибирской медицины, 2020)
Despite the emergence of new groups of drugs for the treatment of type 2 diabetes mellitus (DM2), the issue of optimal adherence to treatment remains of interest.The aim of this study was to investigate the factors that influence the adherence to treatment with sodium glucose co-transporter type 2 inhibitor, empagliflozin (Jardiance, Boehringer Ingelheim, Germany), in patients with DM2.Materials and methods. The study included 102 patients with DM2 (58 of them were women); the observation time was 24 weeks. The mean age was 58.3 ± 10.4 years.Results. Patients without cognitive impairment had a lower level of glycated hemoglobin (HbA1c) (7.76%, 6.18–9.34) than patients with mild dementia (8.51%, 7.02–10; p = 0.032). In the group of patients who noted the impossibility of purchasing even a part of the drugs, the level of HbA1c was 9.73% (8.95–10.51), while patients who had no difficulties in purchasing drugs HbA1c was 8.83% (7.85–9.81; p = 0.036). Empagliflozin was discontinued in 38.2% of patients for the following reasons: cost of the drug (16.6%), development of side effects (10.7%), lack of effectiveness (7.8%), other reasons (2.9%).Conclusion. Thus, the main factors influencing the adherence to treatment were the cost of the drug, development of adverse events, and lack of effectiveness from the therapy. At the same time, the opportunity of purchasing all the necessary drugs was associated with both better glycemic control and a higher quality of life.